High-Flying Research Trends and Innovations in Young Athletes’ Jump Training: A Bibliographic Analysis of Research Over Ten Years - Cahyo Yuwono; Adi S; Mahenderan Appukutty; Erna Setyowati; Bondan Fiqi Riyalda; Hilmy Aliriad; Made Bang Redy Utama (Physical Education Theory and Methodology)
Objectives. This bibliometric study aimed to track the evolution of research trends related to athletic jumps.